Efek minuman cokelat (Theobroma cacao L.) terhadap peningkatan jumlah eritrosit dan kadar hemoglobin tikus putih anemia - Restuti, Arisanty Nur Setia; Yulianti, Adhiningsih; Lindawati, Dewi (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2020)
Background : Anemia is a condition when the body do not have enough healthy red blood cells. Laboratory sign of anemia is decreases of erythrocytes and haemoglobin (Hb) level. Anemia can be caused by deficiency of nutritional intake.Objectives : The purpose of this study was to determine changes inÂ the number of erythrocytes and Â Hb levels of anemia rats which were intervened with chocolate drinks.Methods : The design of this study was an experiment with a pretest-posttest control group design. The samples in this research were 21 male wistar rats. Rats were induced by NaNO2 25mg/gBB for 18 days, then followed by an intervention of chocolate drink 4.3ml / day for 14 days. The results will be tested using one way ANOVA test and paired T-Test.Results : The results of this study showed that there were significant differences in the number of erythrocytes and Hb levels between groups before the intervention (p = 0.00) and (p = 0.011), so also after the intervention there is significant differences in the number of erythrocytes and Hb levels between groups (p = 0.00) and (p = 0.01).Paired T-Test results showed that there were significant differences in the number of erythrocytes and Hb levels before and after the study in the intervention group given chocolate drink (p = 0.00) and (p = 0.02).Conclusion : Chocolate drinks have an effect on increasing the number of erythrocytes and Hb levels in anemia rats.